The Diagnosis and Management of Acute Fatty Liver of Pregnancy - Ahmad Fariz MZ Zein; Irma Wahyuni Anwar; Andri Sanityoso Sulaiman (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Acute fatty liver of pregnancy (AFLP) is a rare catastrophic illness constituting an obstetric emergency in third trimester of pregnancy and may have complications for both mother and fetus, including death. Yet it is still unclear, the pathogenesis of AFLP has been identified related to defects in fatty acid metabolism during pregnancy, especially in the setting of fetal genetic defects in fatty oxidation. Establishing the diagnosis of AFLP is challenging, further it may overlap with other liver diseases of pregnancy, such as preeclampsia and hemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome. The management of AFLP is a multidisciplinary progress providing the prompt intervention more than the termination of the pregnancy. The awareness of AFLP is highly needed to provide early diagnosis and management so that it can reduce the morbidity and mortality.